(untitled) (International Journal of Engineering and Computer Science, 2017)
One important aspect of mobile ad-hoc networks is the group mobility of nodes in topological area, since any node can enter or leave the topological area at any time. The resources are limited with mobile ad-hoc networks, so increasing number of node cannot generate more resources, but they can use and share existing resources with pre-existing nodes in the topological area. An important aspect of group mobility is mobility of nodes inside the group with reference to their leader. Inthis paper we analyze the two protocols AODV and DSDV with equal and unequal distribution of nodes in group.